1999
DOI: 10.1111/j.1748-5827.1999.tb03114.x
|View full text |Cite
|
Sign up to set email alerts
|

Laminectomy for 34 dogs with thoracolumbar intervertebral disc disease and loss of deep pain perception

Abstract: The case details and the results of treatment of 34 dogs with thoracolumbar intervertebral disc disease, without deep pain perception, that had been treated by laminectomy and fenestration, are presented. The association of a number of potential prognostic factors with the neurological outcome is examined. Twenty-one dogs (62 per cent) recovered neurological function, seven (21 per cent) failed to recover neurological function and three (9 per cent) developed progressive myelomalacia postoperatively, while thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
199
3
12

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(234 citation statements)
references
References 13 publications
20
199
3
12
Order By: Relevance
“…Our results show that dogs with loss of CPP have a low rate of recovery compared to 3 previous studies regarding dogs with T3‐L3 SCI and intervertebral disk herniation (58%,4 62%,11 and 58%16). In our study, of 13 dogs with loss of CPP and a L4‐S3 SCI lesion, only 1 dog had a complete functional recovery within 3 weeks (i.e, only 7.7% regained ambulation and continence) and only 3/11 (27%) dogs had a successful long‐term outcome.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Our results show that dogs with loss of CPP have a low rate of recovery compared to 3 previous studies regarding dogs with T3‐L3 SCI and intervertebral disk herniation (58%,4 62%,11 and 58%16). In our study, of 13 dogs with loss of CPP and a L4‐S3 SCI lesion, only 1 dog had a complete functional recovery within 3 weeks (i.e, only 7.7% regained ambulation and continence) and only 3/11 (27%) dogs had a successful long‐term outcome.…”
Section: Discussioncontrasting
confidence: 69%
“…Where possible, clinical records were used to establish whether functional recovery occurred within 21 days of presentation. We chose 21 days based on previous studies showing that recovery of pain sensation in dogs with severe spinal cord injury occurred within 3 weeks in most dogs that later made a good recovery 4, 11. Functional recovery of ambulation was defined as being able to walk without assistance (as we judged that owners would easily be able to answer this question), and functional recovery for urinary continence was defined as having voluntary control of urination (posturing to urinate) without having incidents of accidental urination.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with previous studies,11, 12, 13, 14, 15, 41, 42 45.7% of grade 5 dogs became ambulatory within 6 weeks, compared with 100% of grade 3 and 4 dogs. While the regression tree for the OFS outcome measure revealed conflicting effects of total duration of anesthesia in a small subgroup (Fig 1), considering the similar findings in the regression tree analysis for ambulatory status (Fig 3) as well as the final general linear and ridge regression models, the predominant relationship identified in grade 5 dogs was a poorer outcome with increased duration of surgery (Figs 1, 3; Tables 3, 5).…”
Section: Discussionsupporting
confidence: 90%
“…Another limitation of the current study is the lack of longer term follow‐up data beyond 6 weeks postoperatively, as some dogs that were nonambulatory at 6 weeks could have gone on to recover ambulatory function in the longer term. However, previous studies have shown that the majority of postoperative functional recovery after SCI in dogs occurs within 4–8 weeks of surgery, supporting this observation time frame 11, 13, 32, 42. To maximize the outcome data available, we used 2 functional scoring systems postsurgery; an ordinal 12‐point score (OFS) and a treadmill‐based gait score (RI), both described and validated previously 31, 35.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation